The Pengaruh Faktor-Faktor Fraud Triangle Terhadap Financial Statement Fraud Pada Perusahaan BUMN Yang Terdaftar Pada Bursa Efek Indonesia - Satria Fathi Alauddin; Ahalik Ahalik (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2023)
The purpose of this study is to examine the effect of the fraud triangle on financial statement fraud using the calculation Beneish m-score on BUMN Companies listen on the Indonesian Stock Exchange (IDX) in 2018- 2019. The fraud triangle consist of pressure, opportunity, and rationalization. In this study, the sample was selected using a purposive sampling technique to get as many 17 BUMN companies in 2018-2019. The analysis technique used in this research is panel data regression. The result of this study examine that the fraud triangle has significant simultaneous effect on financial statement fraud. while partially the result examine pressure has a significant positive effect on financial statement fraud. opportunity partially examine no significant effect on financial statement fraud and rationalization partially examine significant positive effect on financial statement fraud.